Association between living habits, indoor humidity, ventilation and asthma among residents in the tropical regions of China - Chen, Mingming; Zhang, Kun; Zhang, Xin; Gao, Jun; Zhang, Rongguang; Wei, Xiaoli; Cao, Wenting (Frontiers in Public Health, 2023)
We have carefully revised and checked our manuscript mainly according to your comments and suggestions, and answered reviewer's all questions point by point.Please kindly refer to the manuscript and see Response to the Reviewers' Comments for the details. We greatly appreciate the reviewer's thoughtful advice and comments to help improve our study. We would like to re-submit the manuscript for consideration of publication in Frontiers in Public health. We would assure that all of the authors have read and approved the final submitted manuscript, that no portion of the work has been or is currently under consideration for publication elsewhere, and that no portion of the manuscript has been published or posted on the Internet.Please kindly let me know if you have any questions. I look forward to hearing from you soon. Again, many thanks for your assistance.